δ13C of organic matter transported from the leaves to the roots in Eucalyptus delegatensis: short-term variations and relation to respired CO2 - Gessler, A.; Keitel, C.; Kodama, N.; Weston, C.; Winters, A.; Keith, H.; Grice, Kliti; Leuning, R.; Farquhar, G. (CSIRO Publishing, 2007)
Post-photosynthetic carbon isotope fractionation might alter the isotopic signal imprinted on organic matter (OM) during primary carbon fixation by Rubisco. To characterise the influence of post-photosynthetic processes, we investigated the effect of starch storage and remobilisation on the stable carbon isotope signature (delta C-13) of different carbon pools in the Eucalyptus delegatensis R. T. Baker leaf and the potential carbon isotope fractionation associated with phloem transport and respiration. Twig phloem exudate and leaf water-soluble OM showed diel variations in delta C-13 of up to 2.5 and 2 parts per thousand, respectively, with C-13 enrichment during the night and depletion during the day. Damped diel variation was also evident in bulk lipids of the leaf and in the leaf wax fraction. delta C-13 of nocturnal phloem exudate OM corresponded with the delta C-13 of carbon released from starch. There was no change in delta C-13 of phloem carbon along the trunk. CO2 emitted from trunks and roots was C-13 enriched compared with the potential organic substrate, and depleted compared with soil-emitted CO2. The results are consistent with transitory starch accumulation and remobilisation governing the diel rhythm of delta C-13 in phloem-transported OM and fragmentation fractionation occurring during respiration. When using delta C-13 of OMor CO2 for assessing ecosystem processes or plant reactions towards environmental constraints, post- photosynthetic discrimination should be considered.